Optimum placement of emergency response stations for maritime accidents in the Marmara Sea - Altan, Yiğit Can. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2010., 2010)
In order to minimize the environmental effect of oil spill caused by maritime accidents, cleanup work has to begin as soon as possible. For that reason, Emergency Response Stations (ERS) are planned to be located according to possible accident places. But exact coordinates of accidents cannot be known before they happen, optimum location of ERS will be chosen according to stochastic model that depends on probability theory. Parameters which are related with accident place and response time are taken into consideration at this model. Since maritime accidental oil spill will move with wind and current, total response time will be calculated by means of wind and current direction and magnitude probability. By means of all data ERS planned for Marmara Sea, are allocated to optimum locations.
Keywords: Emergency management -- Turkey.